Adaptation Meta-Cognitive as an Educational Tool: Animated Puzzle - Ida Syakirah Sudin; Suzana Ahmad; Marina Ismail; Norizan Mat Diah (Institute of Advanced Engineering and Science, 2018)
Students need to be equipped with high order thinking skill in order to prepare them with future world. Eventhough variety of programs on teaching high order thinking skills has been implemented formally in schools in Malaysia and also placed in the school curriculum, the results are not to the satisfactory. This research is proposing a suitable educational tool which can increase higher thinking skills among students. Keeping in mind that learning is a conceptualized multidimensional development involving three components: cognitive learning achievement, meta-cognition and motivation, an educational game with Meta-cognitive activity is proposed. An animated puzzle game that adapts acitivities that enables to nurture meta-cognitive skills has been developed and tested. Heuristic testing and functionality testing has been done towards the project prototype and positive results has been obtained. An enhancement of prototype will embark a new perspective of educational mechanism and could improve students higher order thinking skills capability.